Highly Accurate Analysis of the Cervical Neural Tract of the Elderly Using ZOOM DTI - Sho Furuya; Motoyuki Iwasaki; Takumi Yokohama; Daisuke Ohura; Tomoyuki Okuaki (Neurospine, 2018)
Background/Aims To investigate the fractional anisotropy (FA) values of the cervical spinal cord in elderly individuals using zonally magnified oblique multislice (ZOOM) diffusion tensor imaging (DTI). Methods Fourteen healthy elderly volunteers (group E) and 10 young volunteers (group Y) were enrolled. We assessed the FA, apparent diffusion coefficient (ADC), and λ1–λ3 values using 3-T magnetic resonance imaging. The region of interest was contoured entirely inside the spinal cord, with no gray/white matter distinction, in order to avoid including the cerebrospinal fluid. Results As lower cervical levels were approached, the FA values gradually decreased, while the ADC values increased. The mean FA values at each cervical level were as follows in groups E and Y: 0.71 and 0.70 at the C2/3 level, 0.66 and 0.66 at the C3/4 level, 0.63 and 0.62 at the C4/5 level, 0.57 and 0.57 at the C5/6 level, and 0.58 and 0.57 at the C6/7 level, respectively. The mean ADC values in groups E and Y were 1.06 and 0.99 at the C2/3 level, 1.05 and 1.06 at the C3/4 level, 1.14 and 1.06 at the C4/5 level, 1.18 and 1.21 at the C5/6 level, and 1.39 and 1.46 at the C6/7 level, respectively. There were no significant differences between the elderly and young participants. Conclusion In both asymptomatic elderly and young individuals, the FA values gradually decreased and the ADC values increased moving towards lower cervical levels. Age did not affect the FA values, even though mild cord compression was evident due to spondylotic changes. ZOOM DTI has the potential to provide more information than conventional DTI.